Forced resonant vibrations and dissipative heating of rigidly fixed viscoelastic plates with actuators with regard for a geometrical nonlinearity and transverse shear strains - Karnaukhov, V.G.; Кozlov V.І.; Karnaukhova, T.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
A model of forced resonant vibrations and the dissipative heating of rigidly fixed viscoelastic plates with piezoactuators with regard for a geometrical nonlinearity and transverse shear strains is considered. By the Bubnov—Galerkin method, the approximate analytic solution of this problem is given. The influence of these factors on the effectiveness of the active damping of vibrations by piezoactuators is analyzed.